PELANGGARAN ASAS DALAM PENYUSUNAN DAN PENGESAHAN UNDANG-UNDANG CIPTA KERJA - Disurya, Ramanata; Suryati, Suryati; Sardana, Layang (Faculty of Law, University of Palembang, 2021)
After the passage of the final draft of the Job Creation bill into a Law, many groups objected to this act from various points of view, both procedural and substance. The purpose of this research is to discover the violations of the principles in the preparation and ratification of the Job Creation Law. The method used for this research is normative legal research. The results of this research are the Job Creation Law violates several principles in general such as, (1) The principle of accuracy if it is related to the General Principles of Proper Government Administration, (2) The principle of participation when referring to article 1 paragraph (2) UUD 1945 and Law number 12 of 2011, (3) The principle of constitutionality related to the Omnibus Law